2019
DOI: 10.1111/ene.14136
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term risk of stroke and its predictors in transient ischaemic attack patients in Germany

Abstract: Background and purpose Little is known about the long‐term association between transient ischaemic attack (TIA) and stroke. Therefore, the goal of this study was to analyze the long‐term risk of stroke and associated predictors in a large cohort of TIA patients followed in general practices in Germany. Methods This study included patients with an initial TIA diagnosis and subsequently followed up in one of 1262 general practices in Germany between January 2007 and December 2016 (N = 19 824 patients). The prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
(51 reference statements)
0
6
1
Order By: Relevance
“…The current study also found that cases had more vascular incidents at follow-up than controls (recurrent TIAs, strokes and myocardial infarctions). The relative hazards of death were a little higher than previously reported 8,16,21 . Hence, our study suggests that TIA should not be considered as a 'minor' neurological condition.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…The current study also found that cases had more vascular incidents at follow-up than controls (recurrent TIAs, strokes and myocardial infarctions). The relative hazards of death were a little higher than previously reported 8,16,21 . Hence, our study suggests that TIA should not be considered as a 'minor' neurological condition.…”
Section: Discussioncontrasting
confidence: 63%
“…Some previous studies were often limited by small sample sizes [17][18] or short follow-up periods 19 . Furthermore, comparison of their results was limited due to methodological differences: prospective [16][17] versus retrospective follow-up 8,20 , the source of participants: hospital based 8,16 versus community based 15,18,21 , by stroke etiology, recruitment period and non-adjustment of confounding factors.…”
Section: Introductionmentioning
confidence: 99%
“… 9 Rathmann et al demonstrated good agreement between the outpatient DA database with German reference data with respect to the incidence or prevalence of cancer diagnoses. 9 Finally, this database has already been used in previous studies focusing on cardiovascular disorders 10 , 11 as well as cancer. 12 , 13 …”
Section: Methodsmentioning
confidence: 99%
“…Thus, studies describing the prevalence rates in patients aged ≥65 years were considered. Men have been found to be at a higher risk for developing delirium (1) and other diseases (Angele et al, 2014; Jacob et al, 2019). This also applies to patients aged ≥65 years.…”
Section: Discussionmentioning
confidence: 99%